Epistemologi Kurikulum Pendidikan Sains - Humaidi, Humaidi (Jurnal Pendidikan Islam, 2013)
Curriculum is used as well as the way, plans, rules, teaching materials, and guidelines in the learning process. It is also meaningful as a map of reality. Curriculum is similar as a road map and a map of the world that becomes a guidance and direction for people who are traveling. Curriculum is a map of reality because it becomes a clue, for example, any form of reality and physical, metaphysical, mathematical, social-that can be reviewed and learnt by humans. As a map, it serves as a guideline to observe, to read, and to review some forms. In addition, the curriculum can be functioned and used as a tool by people to actualize their potency, so they can be professional in education.